(untitled) (Vietnam Journal of Community Medicine, 2025)
Objective: To analyze the current status of the distribution and structure of the pharmacy workforce in the Mekong delta region of Vietnam. Methods: A cross-sectional descriptive study was conducted, surveying 2614 pharmacy personnel working at 133 public general hospitals in the Mekong delta region as of December 31, 2022. Results: University-educated pharmacists constituted 46.6% of the workforce, while personnel with college and intermediate diplomas in pharmacy accounted for 53.1%, and pharmacy assistants comprised approximately 0.3%. A marked disparity was observed in the pharmacy workforce structure among provinces, as well as between urban and rural areas. In the majority of the region’s provinces, the ratios of pharmacists/college and intermediate diplomas in pharmacy, pharmacists to physicians, and pharmacists to hospital beds fell below the benchmarks stipulated in Circular 03/2023/TT-BYT. The distribution of pharmacists across general hospitals was also inequitable, with an average of only 6.8 pharmacists per hospital. Notably, 18 hospitals (13.5%) were found to have no pharmacists on staff. Conclusion: In the Mekong delta region, the proportion of pharmacists is low, with the workforce being predominantly composed of college and intermediate diplomas in pharmacy. A significant imbalance in the pharmacy workforce structure persists between urban and rural areas. Furthermore, the ratios of pharmacists to hospital beds, physicians, and per hospital remain at critically low levels.